Differences in use of bryophyte species in tit nests between two contrasting habitats: an urban park and a forest. Issue 1 (1st January 2021) - Glądalski, M.; Wolski, G. J.; Bańbura, M.; Kaliński, A.; Markowski, M.; Skwarska, J.; Wawrzyniak, J.; Bańbura, J.
Abstract: A considerable number of avian species tend to use bryophytes as nest construction material, but the selectivity of birds in their bryophyte use in nest construction in relation to the availability of particular mosses in individual territories remains largely unexplored. We studied the bryophyte composition of nests in two passerine species: the Blue Tit Cyanistes caeruleus and the Great Tit Parus major in two floristically and structurally contrasting study areas (a mature deciduous forest and an urban parkland). We also studied territories within a radius of 10 m from each occupied nest box, listing all bryophyte species and checking to what extent the moss composition of the nest reflected what was available in the surrounding of the nest box. Both tit species appeared to be selective. The tits used a total of 31 bryophyte species in their nests (27 found in Blue Tits and 19 in Great Tits), whereas 25 additional bryophyte species were found around (10 m radius) the studied nests, but not in the nests. The number of bryophyte species found in individual nests varied in the urban parkland between 1 and 6 and in the forest between 1 and 11. The average number of bryophytes in the nest ranged from 2.31 in Great Tit from the urban parkland to 3.52 in Blue Tit in the urban parkland. Only a few species were used in a higher proportion than 5% of the volume within a single nest and, considering only these most abundant bryophyte species, the mean number ranged from 1.28 in Great Tits in the forest to 1.57 in Blue Tits in the urban parkland. Our study also showed that, in general, the bryophyte species composition of the nests seems to be affected by the site (the urban park vs the forest) rather than the parid species (Blue Tit vs Great Tit).